Undernutrition and Associated Factors among Lactating Women: Community-Based Cross-Sectional Study in Moyale District, Borena Zone, Southern Ethiopia - Hailu Bekele; Gebi Husein Jima; Ashenafi Habtamu Regesu (Advances in Public Health)
Background. Undernutrition is one of the most widespread public health problems that affect both developed and developing countries. In Ethiopia, it is one of the factors leading to unacceptable high morbidity and mortality among women. However, little is documented on undernutrition among lactating women particularly in such a purely pastoral community. Therefore, this study was designed to assess prevalence of undernutrition and its associated factors among lactating women living in pastoral community of Moyale District, Borena Zone, Southern Ethiopia, 2018. Methods. A community-based cross-sectional study was conducted. Data were collected from a random sampled 545 lactating women using structured interviewer-administered questionnaire. Height and weight measurements of the study participants were also taken to compute body mass index. Data were entered in to Epi info version 7 and then exported to SPSS version 21 software for analysis. Descriptive statistics like frequency, mean, and percentage were computed to describe characteristics of the sample. Multivariable analysis was carried out, association between independent and dependent variables were measured using adjusted odds ratios, and its 95% confidence interval and P value below 0.05 were considered statistically significant. Results. This study showed that prevalence of undernutrition among lactating women was 17.7%. Dietary diversity (AOR = 2.49, 95% CI: 1.43–4.36), monthly income (AOR = 5.22, 95% CI: 1.40–19.40), extra meal taking (AOR = 2.76, 95% CI: 1.43–5.29, delivery place (AOR = 2.65, 95% CI: 1.24–5.65), and household food insecurity (AOR = 6.57, 95% CI: 3.50–12.34) were independent variables showing statistically significant association with undernutrition of lactating women. Conclusion and recommendations. The study revealed that magnitude of undernutrition among lactating women was high. Dietary diversity, monthly income, extra meal, delivery place, and household food insecurity were found to be predictor of undernutrition. Finally, we recommend that governmental and nongovernmental organizations should organize timely interventions targeting lactating women.